Academic brands : distinction in global higher education / edited by Mario Biagioli, Madhavi Sunder. - Biagioli, Mario, 1955-; Sunder, Madhavi (Cambridge University Press, 2022)
The first comprehensive analysis of the emergence of academic brands, this book explores how the modern university is being transformed in an increasingly global economy of higher education where luxury is replacing access. More than just a sign of corporatization and privatization, academic brands provide a unique window on the university's concerns and struggles with conveying 'excellence' and reputation in a competitive landscape organized by rankings, while also capitalizing on its brand to generate revenue when state support dwindles. This multidisciplinary volume addresses topics including the uniqueness of academic brands, their role in the global brand economy of distinction, and their vulnerability to problematic social and political associations. By focusing on brands, the volume analyzes the tensions between the university's traditional commitment to public interest values - education, research, and the production of knowledge - and its increasingly managerial culture framed by corporate, private values. Available as Open Access on Cambridge Core.